Activity of an A-L-Rhamnosidase Produced by Aspergillus niger During Solid State Fermentation of Coffee Pulp Wastes - Muzakhar, Kahar; Winarsa, Rudju (Jurnal Biodjati, 2019)
Â An Î±-L-Rhamnosidase released by Aspergillus niger during solid-state fermentation (SSF) using coffee pulp (CP) wastes media has been investigated. The activity of Î±-L-Rhamnosidase based on reducing sugar production against 2% CP alkali extract substrate in 50 mM acetate buffer pH 5. The maximum activity of Î±-L-Rham-nosidase was obtained in sixth-day SSF with reducing sugar pro-duction of 13 Î¼g/mL. The enzyme is actively hydrolyzed 0.1% p-ni-trophenyl-Î±-L-rhamnopyranoside (PNP-Rha) to 95% from initial concentration. Purification using DEAE-Toyopearl 650M increased hydrolysis activity ten times against the substrate, reaching 134 Î¼g/mL of reducing sugar. Optimum enzyme activity at pH 4.5 and 50Â°C, while stable at pH and temperature in a pH range of 3.5-7 and below 50Â°C.Â